Changes in Transport Patterns in the Light of External Environmental Risks - Keresztes, Gabor; Meszaros, Katalin; Nemeth, Nikoletta (INTI International University, 2023)
Our research aimed to explore the extent to of the effects of recent global socio-politicaleconomic events (e.g. the pandemic, the Ukrainian-Russian war, the energy crisis, and inflation) have influenced and changed people's transport habits, disaggregated by age groups. The survey was conducted in Hungary in May-June 2023 using an online questionnaire survey. We assume that based on social habits, people, regardless of age, prefer public transport over private cars. People like more walking or cycling to work or school when they can, and most of them do not use cars for small shopping trips either. In terms of car use, the use of electric or hybrid vehicles is less relevant in Hungary, while petrol or diesel cars predominate. We found out that people's transport habits have changed in recent years due to external negative impacts on society. During the pandemic, there was a shift away from public transport, but now that the pandemic is over, the energy crisis and inflation (e.g. significant fuel price increases) have led most people to prefer alternative means of transport and public transport options. Quantitative research results showed that the under-18s in Hungary mainly walk or travel by bus and bicycle, young people aged 18-25 go on foot, by car, bus, and train, the 26-55 age group by car, car and on foot, the 56-65 age group by car and on foot and the older generation (66+) on foot, by bicycle, bus, and car. A higher proportion of respondents between 36-45 years use diesel vehicles and a higher proportion of respondents aged 18-35 and 46-65 years use petrol vehicles. Inflation and changes in energy prices have increased the use of bicycles in all age groups. Bus and train use has increased in the age groups under 18, 18-25, 46-55, and over 66. The use of private cars fuelled by petrol or diesel increased only in the 26-35 age group. There is also an increasing tendency towards walking in all age categories.